DEVELOPMENT OF Lesson MATERIALS FOOD CHEMISTRY BASED ON WEB - Nopriawan Berkat Asi (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2017)
Food Chemistry is one of the elective courses in Chemistry Education Program of University of Palangka Raya. Development of food chemistry materials based on web as an effort to utilize the available computer and internet facilities. One of the advantages of teaching materials based on web is to make it easy for students to access the learning materials after classroom learning. Utilization of computer technology and internet as media development of web-based teaching materials in Chemistry Education Program of University of Palangka Raya is expected to improve the quality of learning. For lecturers and students can provide easiness in the archiving of teaching materials, easy access to open the archives of teaching materials, the ease of doing improvements in teaching materials and ease in the updating of teaching materials. The method of developing food chemistry materials based on web used is the Educational Research and Development method, which is abbreviated as R & D. Gall et al. (2003) states R & D is a process used to develop and validate educational products. This development uses research methods and development of 3D models, namely Define, Design, and Develop, modification 4D Thiagarajan model. In the study conducted a limited-scale trial. Food chemistry materials based on web in the form of learning websites with the address www.kimiakesehatan.blogspot.co.id worthy to be used as a medium of teaching materials in Chemical Education Study Program of University of Palangka Raya.